Selecting respondents for survey questionnaire in Islamic way - Shah, Asadullah; Ahsan, Zubair; Bukhari, Fahad Shah; Abbas, Mohamed; Shah, Faisal Ahmad (Journal of Islamic, Social an, Economics and Development, 2017)
The main objective of this study is to identify key attributes of a respondents to deem him worthy and reliable for the purpose of a survey questionnaire. These key attributes are based on the teachings of the Quran. As the holy Quran is the world of Almighty Allah and it contains absolute knowledge. In this paper, various human traits are identified and described in the light of Quran to determine whether a person can be a respondent in a survey questionnaire study or not.This paper also highlights the types of questions in survey questionnaire and distinguishes which type of questions are used for qualitative and /or quantitative research. Additionally, this paper emphasize on the problems with data collection and samplings, as well as stresses on the problems of probabilistic and non-probabilistic sampling.